Toward Digital Community Policing: Opportunities and Barriers for Social Media Engagement in Indonesia - Herlydinata, Meydiarsyah Dharma (Indonesian National Police Academy, 2025)
This study explores the readiness and challenges of integrating social media into community policing in Indonesia. It aims to identify both opportunities and barriers faced by law enforcement, focusing on how digital platforms can improve trust, accessibility, and responsiveness. Through a structured literature review, it examines practical, legal, and institutional factors affecting effective digital engagement. This study uses a qualitative literature review method, analyzing academic articles, official regulations, and policy reports related to community policing and social media. The approach focuses on identifying recurring themes, theoretical insights, and practical challenges to understand how digital tools can support or hinder community policing efforts in the Indonesian context.The study finds that social media presents key opportunities for community policing, such as increased reach, real-time interaction, and enhanced public trust. However, barriers such as digital illiteracy, misinformation, legal uncertainty, and a lack of officer training remain significant. Successful implementation requires institutional support, clear guidelines, and ethical, consistent engagement across digital platforms.The study concludes that while social media can enhance community policing in Indonesia, its success depends on proper training, legal clarity, and ethical use. Digital engagement should be seen as a core policing function, not an add-on. With the right support and strategy, it can build stronger public trust and more responsive police-community relationships.